Enzymatic Acidolysis of Fish Oil with Milk Fat Fatty Acids for the Synthesis of Structured Lipid - Subroto, Edy; Tensiska; Indiarto, Rossi; Mahani; Mihayudhathie, Nadya Firstyani; Fauzia, Annisa Rizky (Pakistan Journal of Nutrition, 2019)
Background and Objective: Structured lipids (SLs) consisting of saturated fatty acids (SFAs) at the outside position (sn-1,3) and polyunsaturated fatty acids (PUFAs) at the sn-2 position have good nutritional values and high stabilities for oxidation. The objective of this research was to synthesize SLs containing SFAs at the sn-1,3 position and PUFAs at the sn-2 position by the enzymatic acidolysis of fish oil with milk fat fatty acids (MFFAs). Materials and Methods: Fish oil, containing high PUFAs, was combined with milk fat that was hydrolyzed to MFFAs through saponification with KOH followed by acidification with HCl and extraction with hexane. SLs were synthesized by acidolysis using a specific lipase from Mucor miehei. The factors of substrate ratio and reaction time were studied. The SLs were analyzed for the fatty acid compositions, acylglycerol profiles and positional distributions of the fatty acids at sn-2 and sn-1,3. Results: The increasing proportions of the MFFAs and the increase in the reaction time increased the incorporation of SFA into the SLs. An acidolysis ratio of fish oil to MFFAs of 1:3 and a reaction time of 6 h at 40°C resulted in a good SL, where EPA and DHA were incorporated at sn-2 at 13.20 and 12.85%, respectively and SFAs (capric, lauric, myristic, palmitic and stearic acids) at sn-1,3 at approximately 58.25%. The SL had an acylglycerol profile containing triacylglycerol (TAG), diacylglycerol (DAG) and monoacylglycerol (MAG) at 69.45, 22.32 and 8.23%, respectively. Conclusion: The optimum enzymatic acidolysis conditions for synthesizing the SL were a molar ratio of fish oil to MFFAs of 1:3 and a reaction time of 6 h at 40°C. The SL has the potential to fortify high-nutrition dairy products.